Turistifikasi Pariwisata Bali: Studi Kasus Kebijakan Penyediaan Fasilitas Di Daya Tarik Wisata Pura Agung Besakih, Bali (Jurnal Destinasi Pariwisata, 2025)
This study discusses the process of touristification in Bali tourism, with a focus on a case study of facility provision policies at the Pura Agung Besakih tourist attraction. Touristification refers to the phenomenon of local spaces and cultures being transformed into tourist products as a result of increased tourism activity. Touristification often involves changes in governance, infrastructure, and social interactions among local communities. Pura Agung Besakih is the largest temple in Bali and serves as a place of worship for the Hindu community. However, with the development of tourism in Bali, Pura Agung Besakih has also evolved into a tourist attraction that attracts visitors. In providing facilities at the Pura Agung Besakih tourist attraction, it is necessary to adhere to existing policies to ensure that such facilities do not infringe upon or exceed the boundaries of the sacred area of Pura Agung Besakih. The Karangasem Regency Regulation No. 17 of 2012 on the Spatial Planning of the Karangasem Regency for the years 2012-2032 is used as a reference for policy in this study. The research method employed is qualitative descriptive, utilizing data collection techniques such as observation, structured interviews, documentation, and literature review.The research results indicate that the majority of the local community around Pura Agung Besakih are employed in the tourism sector, with most working as merchants. Additionally, the local community must adapt to the language used when interacting with international tourists. The utilization of zones in the Pura Agung Besakih area is divided into two zones: the Utamaning Mandala zone and the economic zone. In the Utamaning Mandala zone, utilization outside of religious activities is not permitted, while in the economic zone, utilization outside of religious activities is permitted. Facilities are divided into two categories: built facilities and non-built facilities, which are intended for tourists and visitors (pemedek) and are subject to regulations that tourists must comply with when visiting the tourist attraction of Pura Agung Besakih.
Keywords: Touristification; Policy; Temple; Tourist Attraction; Provision of Tourism Facilities